Assistance in the Formation of Village Policy Regarding Child Protection in the Sigar Penjalin Tourism Village, Tanjung District, North Lombok Regency - Aswadi, Khairul; Rauzi, Fathu; Kamil, M. Ikhsan (Abdi Masyarakat, 2024)
Children are a generation successor. The nation's ideals, commitment and treatment that pay attention to the development and role of children as the nation's next generation are things that must be upheld by the leaders of this country. Children who are not yet mentally and physically mature must have their needs met, and be given proper education for their personal and psychological growth and development, so that in the future the children can grow and develop into children who can be expected to be the successors of the nation's ideals. Children have a strategic role in ensuring the existence of the nation and state in the future. So that they will be able to shoulder this responsibility in the future, children need to have the widest possible opportunities to grow and develop optimally, both physically, mentally, socially and spiritually. Children who, because of their condition, have not yet reached a mature level of growth and development are different from adults in general. Government Regions and communities have a very vital role in child protection. This is stated in article-chapter Child Protection Law, one of which is Article 9 paragraph 1 Law Number 35 of 2014. The high number of cases involving children in North Lombok, especially in Sigar Penjalin Village, Tanjung District, is starting to worry. Based on data from UPTD Protection of Children and Women North Lombok, by mid-2023 57 cases involving children have been found. Of the 57 cases, 42 were cases of child marriage and 12 cases were cases of sexual abuse of children. Based on the problems above, it is very necessary to assist in the formation of village policies regarding child protection. It is hoped that from the activity of Forming a Village Policy Regarding Child Protection in the Sigar Penjalin Tourism Village, North Lombok, there will be output in the form of sensitivity of village government officials, members of the Village Consultative Body, Community Figures; increase knowledge and encourage performance in synergy between village government officials, members of the Village Consultative Body and Community Leaders in producing legal products in the form of village regulations that will reduce the number of child problems in Sigar Penjalin Village, Tanjung District.